METODE DAKWAH BAGI MASYARAKAT PEDESAAN - Nur Safitri (INSTITUT AGAMA ISLAM NEGERI METRO, 2023)
Da'wah material is the content of the message conveyed by a da'wah subject to mad'u. The da'wah material in question is the teachings of Islam itself which are sourced from the Qur'an and Sunnah. Therefore, calling for da'wah material means calling on the Al-Qur'an and hadith. Because of the breadth of Islamic teachings, every da'i has no other way, he must always try and not get bored studying the Qur'an and hadith. The da'wah material in question is the teachings of Islam itself which are sourced from the Qur'an and Sunnah. Therefore, calling for da'wah material means calling on the Al-Qur'an and hadith. Because of the breadth of Islamic teachings, every da'i has no other way, he must always try and not get bored studying the Qur'an and hadith.